The thermo-mechanical degradation of ethylene vinyl acetate used as a solar panel adhesive and encapsulant - Badiee, A.; Ashcroft, Ian; Wildman, Ricky D. (Elsevier, 2016)
The thermal ageing of an Ethylene-vinyl Acetate (EVA) polymer used as an adhesive and encapsulant in a photovoltaic module has been investigated. The EVA is used to bond the silicon solar cells to the front glass and backing sheet and to protect the photovoltaic materials from the environment and mechanical damage. Using a range of experimental techniques, including Dynamic Mechanical Analysis, Differential Scanning Calorimetry and Thermo-Gravimetric analysis, it was possible to show a link between changes in mechanical properties with both the transient temperature and the degree of long-time thermal ageing. Importantly, it was possible to show that the ageing related property changes were likely due to long term structural changes rather than any modification of the chemistry of the material.